Does the Overcost Prediction Index Relate to Nursing Service Quality in BPJS Inpatients? - Rustianawati, Yuni; Rusnoto, Rusnoto; Dedi, Blacius (Universitas Muhammadiyah Yogyakarta, 2025)
Health financing through the INA-CBGs system by BPJS Health frequently engenders a discrepancy between the actual hospital tariff and the INA-CBGs tariff. The discrepancy may result in overcosts associated with the quality of nursing services. This study examined the correlation between the overcost prediction index (which encompasses hospital tariffs, disease diagnosis, type of service, and length of stay) and the quality of nursing services in BPJS inpatients. The present study employed a quantitative descriptive method with a cross-sectional design, encompassing 104 BPJS class III inpatients at RSUD dr. Loekmonohadi Kudus, who were selected through a purposive sampling technique. The data were collected using a structured questionnaire tested for validity and reliability, then analyzed univariately and bivariately using Pearson's Chi-Square test. The findings indicated a substantial correlation between the components of the overcost prediction index and the quality of nursing services. This finding is statistically significant and makes a scientific contribution to developing health financing systems and nursing service quality. The practical implications of this study highlight the imperative for periodic evaluation of the INA-CBGs system, the precision of diagnosis coding, and the implementation of theory-based nursing service models to preserve service quality within the limitations imposed by JKN health financing.